Mekanisme Psikologis Servant Leadership terhadap Kepuasan Kerja Karyawan: Sebuah Systematic Literature Review - Jenar Ayu Persada; Valerine Tampubolon; Najwa Aulannisa (Indo Publishing, 2026)
This study examines how servant leadership influences employee job satisfaction using a Systematic Literature Review (SLR) approach. Articles published 2021 and 2026 were collected from databases such as Scopus, ScienceDirect, SpringerLink, and ProQuest. The findings indicate that servant leadership is positively associated with job satisfaction across various organizational contexts. This leadership style enhances trust, strengthens relationships between leaders and employees, and creates a supportive work environment. Furthermore, the result shows that the relationship between servant leadership and job satisfaction operates through psychological mechanisms, such as trust and leader-member exchange, as well as structural mechanisms, including empowerment and employee development. However, the strength of this relationship varies depending on contextual factors, such as organizational culture and individual characteristics. Therefore, organizations are encouraged to implement servant leadership by considering internal conditions and contextual dynamics.